A global assessment of welfare in farmed fishes: the FishEthoBase - Saraiva, João (2020)
Fish welfare is an essential issue that needs to be tackled by the aquaculture industry. In order to address it, studies have been limited to a small number of species and the information is generally scattered. In order to have a consistent overview of the welfare of farmed fishes, we present the FishEthoBase, an open-access database that ultimately aims to provide information on the welfare of all fish species currently farmed worldwide. Presently with 41 species, this database is directed to all stakeholders in the field and targets not only to bridge the gaps between them but also to provide scientific information to improve the welfare of fish. The current text explains the database and presents an analysis of the welfare scores of 41 species, suggesting that (i) the general welfare state of farmed fishes is poor, (ii) there is some potential for improvement and (iii) this potential is related to research on species’ needs, but (iv) there are many remaining knowledge gaps and (v) current fish farming technologies do not seem to fully address welfare issues. The existence of a framework, such as the FishEthoBase, is proposed as fundamental to the design of strategies that improve the welfare of farmed fish.